KONSTRUKSI KECANTIKAN DI KALANGAN WANITA KARIER (DI KECAMATAN LAMONGAN, KABUPATEN LAMONGAN) - Rukmawati, Deni Ria; Dzulkarnain, Iskandar (DIMENSI, 2015)
In modern era such as today women needs continues to spread, especially on the beauty matters. So they always trying to maintenance her body in order to be beautiful and attractive. This study investigates how beauty construction undertaken by career women in the District Lamongan, Lamongan. This study used qualitative methods and methodological this research based on phenomenological approach. Informant selected using purposive sampling by using triangulation with the source that is comparing and checking the degree of confidence behind the information obtained through different interviews in retrieving information.The results showed that, in shaping beauty among career women, the work environment is the main factor. And unwittingly they are a form of mass media (advertising). In this study also shows that the nature of consumerism in women who do beauty treatments, today beauty be a part of their lifestyle to become a modern feminist woman.